Chiral Surface and Geometry of Metal Nanocrystals. Issue 41 (13th December 2019) - Im, Sang Won; Ahn, Hyo‐Yong; Kim, Ryeong Myeong; Cho, Nam Heon; Kim, Hyeohn; Lim, Yae‐Chan; Lee, Hye‐Eun; Nam, Ki Tae
Abstract: Chirality is a basic property of nature and has great importance in photonics, biochemistry, medicine, and catalysis. This importance has led to the emergence of the chiral inorganic nanostructure field in the last two decades, providing opportunities to control the chirality of light and biochemical reactions. While the facile production of 3D nanostructures has remained a major challenge, recent advances in nanocrystal synthesis have provided a new pathway for efficient control of chirality at the nanoscale by transferring molecular chirality to the geometry of nanocrystals. Interestingly, this discovery stems from a purely crystallographic outcome: chirality can be generated on high‐Miller‐index surfaces, even for highly symmetric metal crystals. This is the starting point herein, with an overview of the scientific history and a summary of the crystallographic definition. With the advance of nanomaterial synthesis technology, high‐Miller‐index planes can be selectively exposed on metallic nanoparticles. The enantioselective interaction of chiral molecules and high‐Miller‐index facets can break the mirror symmetry of the metal nanocrystals. Herein, the fundamental principle of chirality evolution is emphasized and it is shown how chiral surfaces can be directly correlated with chiral morphologies, thus serving as a guide for researchers in chiral catalysts, chiral plasmonics, chiral metamaterials, and photonic devices. Abstract : The fundamentals needed to crystallographically define the surface chirality in metal are summarized, and synthetic strategies to produce the corresponding chiral geometries by controlling chiral high‐Miller‐index facets are provided. The surface and overall geometry are linked, and thus a guide for producing various chiral metallic nanoparticles for metamaterials, biosensors, catalysts, and optical applications is given.